A rational exploration of personalist bioethics: understanding its foundations - Jaime Hernandez-Ojeda; Pablo Requena (Health for All Nations, 2024)
The aim of this article is to elucidate the rational foundations upon which personalist bioethics is built, thereby enhancing understanding regarding its place within the broader discourse of secular bioethics. Personalist bioethics, as a dynamic pursuit, actively engages with scientific discoveries, periodically revisiting them and considering contemporary individualsʼ diverse perceptions of identity and values. It integrates two foundational trunks: personalism and Aristotelian-Thomistic theology with metaphysical reference. The method employed by personalist bioethics is illustrated through triangulation: the exposition of biomedical reality, an in-depth study of anthropological significance, and the identification of values at stake. Rooted in a substantialist concept of the human person, it follows a systematic interaction of various knowledge spheres, aiming not only to describe problematic relations but also to propose prescriptive solutions. Personalism maintains that the human person is valuable for who he is and not only for the choices he makes; he is a source from which the choices proceed. According to personalist ethics, the ethical value of an act will have to be considered under the subjective aspect of intentionality, but it will also have to be considered in terms of its objective content and its consequences. The natural moral law that urges every conscience to do good and avoid evil, therefore, becomes concrete in respect for the human person in all the fullness of his values, his essence, and ontological dignity.